Kekuasaan Kyai dalam Komunitas Pesantren Khusus Waria Senin-Kamis Al-Fatah Notoyudan Pringgokusuman Gedongtengen Yogyakarta - Supriadi, Endang (Jurnal Sosiologi Agama, 2014)
Power is the ability of individuals or groups to impose their will on other people, though there is resistance, through rejection, either in the form of withholding reward provided or in the form of punishment. Max Weber defines power as the ability of individuals or groups to instruct something on other people. As for the powers of Kyai in Pesantren Khusus Waria is symmetrical (balanced). There is no super-ordination and subordination. So power of Kyai is not absolute. Certainly there are factors which constitute power of kyai in Pesantren Khusus Waria not absolute. The first is identity. The second is situation of religion. The third is prayers. Those situations illustrate the fact that happens in Pesantren. Students are able to define something they know, so what is the result of interaction with environment can be implemented in accordance with their abilities. Nevertheless, they still respect kyai. Because of his guidance the students in Pesantren can have knowledge of religion.